First San Jose State Normal School building. - Unknown:::Creator::::::::::::
Caption on back of photograph: 'San Jose State Normal School-destroyed by fire in 1880; erected in 1870.' "San Jose State Normal School was a Romanesque-style, wooden building that included administrative offices, classrooms, library, museum, lecture hall, and recital hall. Built at a cost of $285,000, it was considered one of the most beautiful buildings in the state. In the early morning on February 10, 1880 a fire broke out in the Normal School. The magnificent wooden structure burned fiercely and was totally destroyed."